2002
DOI: 10.1124/jpet.102.039198
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of α7 Nicotinic Acetylcholine Receptors in Gene Expression of Dopamine Biosynthetic Enzymes in Rat Brain

Abstract: Brain dopaminergic systems are critical in mediating the physiological responses to nicotine. The effects of several concentrations of nicotine (0.08, 0.17, or 0.33 mg/kg body weight) and involvement of ␣7 nicotinic acetylcholine receptors (nAChRs) in gene expression of key enzymes in dopamine biosynthesis were evaluated in the ventral tegmental area (VTA) and substantia nigra (SN), cell bodies of the mesocorticolimbic and nigrostriatal pathways. Nicotine elicited a dose-dependent elevation of mRNA for tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
33
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
6
33
0
1
Order By: Relevance
“…278 intraventricular administration of a GABA A receptor agonist (Soriano et al 1997, Yamada et al 1996; SNc TH mRNA is elevated followed systemic administration of nicotine or α-7 nicotinic acetylcholine receptor agonists (Serova & Sabban 2002); and we recently reported that the number of SNc TH+ cells in adult mice can be increased or decreased by direct brain infusions of drugs targeting SNc neuronal activity (Aumann et al 2011, Aumann et al 2008. These data are consistent with the possibility that the DA phenotype of adult SNc neurons can be gained or lost in an activity-dependent way.…”
supporting
confidence: 76%
“…278 intraventricular administration of a GABA A receptor agonist (Soriano et al 1997, Yamada et al 1996; SNc TH mRNA is elevated followed systemic administration of nicotine or α-7 nicotinic acetylcholine receptor agonists (Serova & Sabban 2002); and we recently reported that the number of SNc TH+ cells in adult mice can be increased or decreased by direct brain infusions of drugs targeting SNc neuronal activity (Aumann et al 2011, Aumann et al 2008. These data are consistent with the possibility that the DA phenotype of adult SNc neurons can be gained or lost in an activity-dependent way.…”
supporting
confidence: 76%
“…Some workers have shown that severe stress, chronic nicotine treatment, or reserpine treatment induces TH gene expression in midbrain, with those neurons having their cell bodies in the ventral tegmentum being more responsive than those with their cell bodies in the substantia nigra (Pasinetti et al, 1990;Ortiz et al, 1996;Serova and Sabban, 2002). However, this induction has not been observed in other studies and when observed, the effects are usually small or short-lived compared with those seen in adrenal medulla or locus coeruleus (Biguet et al, 1986;Smith et al, 1991;Melia et al, 1992).…”
mentioning
confidence: 71%
“…In further support of our demonstrated lack of confound status for NL use, haloperidol administration has not been shown to decrease biopterin levels in the nigrostriatal system of 6-OHDA-lesioned rats [42] . Smoking has not been assessed as a potential confound in this study; however, evidence from the literature indicates that schizophrenics are signifi cantly more likely to be smokers than controls [43,44] , and that nicotine elevates levels of GTPCH mRNA and biopterin [45][46][47] . Greater nicotine exposure for schizophrenics then would likely not account for the biopterin defi cit we have observed in our schizophrenic sample.…”
Section: Discussionmentioning
confidence: 99%